Observer reactions to interpersonal injustice: The roles of perpetrator intent and victim perception. (30th May 2012) - Umphress, Elizabeth E.; Simmons, Aneika L.; Folger, Robert; Ren, Run; Bobocel, Ramona
Summary The present research contributes to a growing literature on observer reactions to injustice experienced by others. In particular, we separated two variables that have previously been confounded in prior research, namely perpetrator intent to cause harm and victim perception of harm. We expected that injustice intent and injustice perceptions would have both unique and joint effects on observer reactions. The results of three experiments in which we manipulated perpetrator injustice intent and victim injustice perceptions supported our predictions. First, we found that observers had more negative reactions toward superiors who intended to inflict high versus low levels of interpersonal injustice toward a subordinate. Second, the injustice intent of the superior influenced observers' reactions more than did victim perceptions of injustice. Third, most novel, we found that the mere intent to cause injustice generated negative reactions in observers, even in the absence of a "true" victim—that is, when the subordinate perceptions of injustice were low. Together, our results emphasize the importance of examining observers' reactions to injustice and incorporating perpetrator intentions into the study of organizational justice. Copyright © 2012 John Wiley & Sons, Ltd.